Beneficial impact of zinc supplementation on the collagen in the bone tissue of cadmium‐exposed rats. Issue 7 (5th March 2018) - Andrulewicz‐Botulińska, Edyta; Wiśniewska, Róża; Brzóska, Malgorzata M.; Rogalska, Joanna; Galicka, Anna
Abstract: Cadmium (Cd) is a toxic metal that damages bone tissue by affecting its mineral and organic components. The organic matrix is mainly (90%) composed of collagen, which determines the biomechanical strength of bone. The aim of this study was to evaluate the effect of zinc (Zn) supplementation (30 or 60 mg l –1 ) under moderate and relatively high exposure to Cd (5 and 50 mg l –1 ) on collagen in the rat tibia proximal epiphysis and diaphysis (regions abundant in trabecular and cortical bone, respectively). Significant decrease in collagen type I biosynthesis was found in both regions of the tibia in Cd‐treated rats, whereas the supplementation with Zn provided significant protection against this effect. Western blot confirmed the presence of the major type I collagen in the tibia epiphysis and diaphysis, but collagen type II was revealed only in the epiphysis. Acetic acid‐ and pepsin‐soluble collagen concentration in the tibia epiphysis and diaphysis was significantly increased due to the exposure to Cd, whereas the supplementation with Zn protected, partially or totally, from these effects, depending on the used concentration. The supplementation with Zn also provided protection from unfavorable Cd impact on the maturation of the bone collagen, as the ratio of cross‐links to monomers was higher compared to the Cd‐treated group. This report confirms our previous findings on the preventive action of Zn against harmful effects of Cd on bone, but additionally, and to the best of our knowledge for the first time, explains the possible mechanism of the beneficial influence of this bioelement. Abstract : The present paper is the first to investigate the zinc (Zn) protective action against cadmium (Cd)‐induced changes in the biosynthesis and solubility of collagen in the proximal epiphysis and diaphysis (trabecular and cortical bone) of the tibia. The study revealed that Zn (30 or 60 mg l –1 ) supplementation during the exposure to 5 or 50 mg Cd l –1 can protect from Cd‐induced inhibition of collagen biosynthesis and increased collagen solubility; however, the beneficial impact of Zn depends on its intake.